2010
DOI: 10.1186/1471-2458-10-246
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the metabolic syndrome in Pudong New Area of Shanghai using three proposed definitions among Chinese adults

Abstract: Background: The prevalence of metabolic syndrome (MS) has been increasing in China in recent years. The aim of this study is to estimate and compare the prevalence of MS among Chinese adults in Shanghai, one of the most economic developed areas in China, using definitions proposed by World Health Organization (WHO), National Cholesterol Education Program Adult Treatment Panel (modified ATP III) and International Diabetes Federation (IDF). Methods:This cross-sectional study included 5,584 adults at age 20-79 ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 26 publications
6
23
4
Order By: Relevance
“…Furthermore we reported the MS prevalence in 2007–2008 was 21.6% in East China, which was in line with a report of 22.4% in Northeast China22 and in urban Shanghai, East China in 200823. However, our data is lower than that in rural Handan of China in 2006–2007 in which the prevalence of MS was 39.7% and 54.2% in men and women respectively24.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore we reported the MS prevalence in 2007–2008 was 21.6% in East China, which was in line with a report of 22.4% in Northeast China22 and in urban Shanghai, East China in 200823. However, our data is lower than that in rural Handan of China in 2006–2007 in which the prevalence of MS was 39.7% and 54.2% in men and women respectively24.…”
Section: Discussionsupporting
confidence: 91%
“…Several previous studies have reported the prevalence of MetS in Chinese population using various criteria [11,17,18]. The report by Gu et al based on a national survey of Chinese adults aged 35–74 years conducted in 2000–2001 reported that the age-standardized prevalence of MetS was only 9.8% in men and 17.8% in women according to the NCEP ATP III criteria, and 15.1% (13.6% in men and 16.6% in women) using the modified NCEP ATP III criteria [11].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on variations in the prevalence of MetS and combination of metabolic components across countries due to differences in the definition used, the characteristics and the magnitude of metabolic risk factors among the populations [4-7]. The prevalence of the clustering of MetS components was also varied by age and sex [5,8].…”
Section: Introductionmentioning
confidence: 99%